Indian fedualism C.A.D. 300-1200 - Sharma , Ram Sharan (Delhi, 1980)
First published in 1965, the book analyses the practice of land grants, which became considerable in Gupta times and widespread in post-Gupta times. It shows how this led to the emergence of a class of landlords, endowed with fiscal and administrative rights, superimposed upon a class of peasantry overburdened with numerous imposts and deprived of communal agrarian rights. In its early phase the system was marked by the decline of trade, towns and coinage, and it contributed to enormous rural expansion and acculturation of the tribal population.
Keywords: Feudalism